THE EFFECT OF CONCRETE THINGS ON VOCABULARY LEARNING OUTCOMES OF GRADE SEVEN STUDENTS AT SMP NEGERI 13 PALU - Nurfauziah Mansur (Program Studi Pemikiran Politik Islam, Fakultas Ushuluddin, Adab, dan Dakwah IAIN Palu, 2022)
This research aims at finding out the effect of concrete things on students’ learning outcomes in learning vocabulary of grade seven at SMP Negeri 13 Palu. This research applied quasi experimental design, in which there were two groups, experimental and control group. Seventh grade E as the experimental group, while seventh grade F as the control group. This research involved 50 students of SMP Negeri 3 Palu. The samples of this research were taken from the population of grade seven students by using purposive sampling technique. The researcher used tests as the instrument of collecting data. The tests were divided into two; pretest and posttest that were given to the experimental and control group. The treatment was conducted six times which was given to the experimental group by using concrete things, while the control group using the other technique. The data obtained from the test were analysed statistically. From the analysis, there was a difference between the achievement of experimental (85.5) and control group(54.6). It was based on the hypothesis testing done, by using 0.05 level of significance and 48 degree of freedom (df), the researcher found that t-counted (5.11) is higher than t-table (2.0126). It means that the hypothesis (Ha) is accepted or in the other words the use of concrete things has significant effect on students’ learning outcomes in learning vocabulary.